Structural changes induced in nanocrystals of binary compounds confined within single walled carbon nanotubes: a brief review - Sloan, J; Friedrichs, S; Meyer, R; Kirkland, A; Hutchison, J; Green, M (2002)
High resolution transmission electron microscopy (HRTEM) studies of single wall carbon nanotubes containing nanocrystals of inorganic salts and other binary compounds show that the confining geometry of the host tubules substantially modifies the local structural and co-ordination properties of the inclusion materials. © 2002 Elsevier Science B.V. All rights reserved.